1997
DOI: 10.1200/jco.1997.15.11.3388
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer metastatic cells detected in blood by reverse transcriptase-polymerase chain reaction and dot-blot analysis.

Abstract: The RT-PCR dot-blot analysis of CEA mRNA in blood cells seems to be a promising tool for the early detection of micrometastatic circulating cells in patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Interestingly, two patients turned into positive result developed an early relapse or multiple distant metastases one or two months later, respectively. Similar cases were reported in lung cancer, in which the patients with positive CEA mRNA without metastasis, developed metastasis within 6 months of analysis (Castaldo et al, 1997). Long-term follow-up data on gastrointestinal tract cancer, however, has not yet been available, and it is, therefore, uncertain whether the presence of circulating tumor cells reliably indicates poor prognosis.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Interestingly, two patients turned into positive result developed an early relapse or multiple distant metastases one or two months later, respectively. Similar cases were reported in lung cancer, in which the patients with positive CEA mRNA without metastasis, developed metastasis within 6 months of analysis (Castaldo et al, 1997). Long-term follow-up data on gastrointestinal tract cancer, however, has not yet been available, and it is, therefore, uncertain whether the presence of circulating tumor cells reliably indicates poor prognosis.…”
Section: Introductionmentioning
confidence: 62%
“…Interestingly, there have been some reports suggesting the correlation between positivity for CEA mRNA in the peripheral blood and subsequent relapse, e.g., three of 4 positive patients with far-advanced pancreatic carcinoma developed recurrence after curative operation or liver metastasis after mass-reducing operation within 9 months after the analysis (Funaki et al, 1996), two of 4 positive patients without the evidence of distant metastasis developed metastasis within a few months (Castaldo et al, 1997). Also in our previous study, one patients with stage III gastric cancer who was negative for CEA mRNA initially and turned positive during follow-up, developed multiple bone metastasis one month later.…”
Section: Discussionmentioning
confidence: 99%
“…CEA RT-PCR has been used for detection of micrometastases in gastro-intestinal, 13,16,17,[28][29][30][31][32][33][34][35][36][37] breast [13][14][15][16][17][18] and lung 38 cancers. Specificity of the PCR protocol was tested on different healthy control tissues: peripheral blood, 16,17 bone marrow 13 and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Currently no accepted markers exist for early detection. According to previous studies of lung cancer, CEA was detected in 50% 21 or 60% of patients, 4 cytokeratin 19 in 39% of patients 22 and prepro GRP in 30%. 20 Syndecan 1 (CD 138) is a cell surface transmembrane heparan sulfate proteoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been suggested that the RT-PCR method is more rapid and sensitive. 4,21,29,30 PCR methods have been reported for the detection of CEA, 21 CK19, 31 preprogrowth hormone receptor 20 and MUC1 32 from blood samples of lung cancer patients.…”
mentioning
confidence: 99%